Pengaruh Governance, Risk, and Compliance, dan Intellectual Capital terhadap Kinerja Perusahaan dengan Leverage sebagai Pemoderasi - Carolina, Sienny Jesica; Stephanus, Daniel Sugama; Pratama, Bagas Brian (Parsimonia - Jurnal Ekonomi dan Bisnis, 2025)
Financial performance is one of the factors that can show how well a company achieves its goals. Governance, Risk, Compliance (GRC) serves as a new assessment tool to measure a company's financial performance because recently, companies are expected not only to focus on their profits but also on their business environment. The implementation of GRC and IC cannot be separated from the activities of achieving the company's financial performance. The addition of value added to employees will help the implementation of effective governance, risk management, and compliance functions, which is one of the solutions for organizations in both the public and private sectors. This research is quantitative research that uses resource-based theory. The sample used in this research is companies that won the Top GRC Award from 2019 to 2022, both listed and unlisted on the Indonesia Stock Exchange. The independent variables used include governance, risk, compliance, and intellectual capital. The moderating variable used is leverage. The control variable used is company size. The results show that GRC has a significant effect on financial performance, while intellectual capital does not have a significant effect on financial performance. Leverage can only moderate the relationship between GRC and financial performance, and leverage cannot moderate the relationship between IC and financial performance.